A hydrogel wound dressing containing nano-cuttlebone
By using nano-seafoil powder in hydrogel wound dressings, the problem of poor hemostasis effect of traditional dressings is solved, and long-lasting hemostasis and healing support for wounds is achieved.
Patent Information
- Application Number
- CN202411401491.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Traditional wound dressings have poor hemostasis effect, which limits their application and development in the medical field.
Using a hydrogel wound dressing containing nanosquids, nanosquid powders of different particle sizes are distributed in different hydrogel skeletons of the dressing body to achieve a long-lasting hemostatic effect.
By stacking the first and second hydrogel skeletons arranged in a stack, the synergistic effect of large and small nanosea skeleton powders is achieved to achieve long-lasting hemostasis of wounds and support wound healing.
Smart Images

Figure CN119258264B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wound dressings, and in particular to a hydrogel wound dressing containing nano-cuttlebone. Background Art
[0002] In the medical field, the choice of wound dressings is crucial for wound healing. Although traditional wound dressings such as gauze and bandages have certain absorbency and protection, they have many disadvantages, such as easy adhesion to wounds, poor air permeability, and limited hemostatic effect. Among them, the poor hemostatic effect seriously restricts the use and development of wound dressings, so the development of new wound dressings is of great significance. Summary of the invention
[0003] Based on the above problems, the present invention provides a hydrogel wound dressing containing nano-cuttlebone. The hydrogel wound dressing containing nano-cuttlebone has a lasting hemostatic effect, which is conducive to the development of widening the use of wound dressings.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] A hydrogel wound dressing containing nano-cuttlebone comprises a dressing body, wherein the dressing body has a dressing surface and an isolation surface opposite to the dressing surface, wherein the dressing surface is used to cover the wound, and the isolation surface is used to isolate the contact between the environment and the wound; in the direction from the dressing surface to the isolation surface, the dressing body comprises a first hydrogel skeleton and a second hydrogel skeleton which are stacked, wherein a first nano-cuttlebone powder is distributed in the first hydrogel skeleton, and wherein a second nano-cuttlebone powder is distributed in the second hydrogel skeleton; and the particle size of the first nano-cuttlebone powder is greater than the particle size of the second nano-cuttlebone powder.
[0006] In some embodiments, the particle size of the first nano-cuttlebone powder is 200nm~400nm; the particle size of the second nano-cuttlebone powder is 50nm~100nm.
[0007] In some embodiments, the mass percentage of the first nano-cuttlebone powder in the first hydrogel skeleton is greater than the mass percentage of the second nano-cuttlebone powder in the second hydrogel skeleton.
[0008] In some embodiments, the mass percentage of the first nano-cuttlebone powder in the first hydrogel skeleton is 5% to 15%; the mass percentage of the second nano-cuttlebone powder in the second hydrogel skeleton is 2% to 10%.
[0009] In some embodiments, the thickness of the first hydrogel skeleton is greater than the thickness of the second hydrogel skeleton.
[0010] In some embodiments, the thickness of the first hydrogel skeleton is 0.3 mm to 2 mm; the thickness of the second hydrogel skeleton is 0.2 mm to 1.5 mm.
[0011] In some embodiments, the first hydrogel skeleton comprises a first hydrophilic polymer material and a first cross-linking agent; the first hydrophilic polymer material comprises sodium alginate, and the first cross-linking agent comprises calcium chloride;
[0012] The second hydrogel skeleton contains a second hydrophilic polymer material and a second cross-linking agent; the second hydrophilic polymer material includes one or more of polyacrylamide and polyvinyl alcohol, and the second cross-linking agent includes glutaraldehyde.
[0013] In some embodiments, the mass percentage of the first cross-linking agent in the first hydrogel skeleton is 1% to 5%; the mass percentage of the second cross-linking agent in the second hydrogel skeleton is 0.1% to 1%.
[0014] In some of the embodiments, the hydrogel wound dressing containing nano-cuttlebone further comprises a waterproof breathable membrane; the waterproof breathable membrane is located on the isolation surface; the material of the waterproof breathable membrane comprises one or more of polytetrafluoroethylene and polyurethane.
[0015] In some embodiments, the hydrogel wound dressing containing nano-cuttlebone further comprises a protective film; the protective film is located on the dressing surface; and the material of the protective film comprises one or more of polyethylene and polypropylene.
[0016] Beneficial Effects
[0017] The hydrogel wound dressing of the present invention comprises a dressing body, which has a coating surface and an isolation surface opposite to the coating surface. The coating surface is used to cover the wound, and the isolation surface is used to isolate the contact between the environment and the wound. In the direction from the coating surface to the isolation surface, the dressing body comprises a first hydrogel skeleton and a second hydrogel skeleton arranged in a stacked manner, wherein the first hydrogel skeleton is distributed with a first nano-cuttlebone powder, and the second hydrogel skeleton is distributed with a second nano-cuttlebone powder. The particle size of the first nano-cuttlebone powder is larger than the particle size of the second nano-cuttlebone powder. When the wound dressing is used, the wound is covered by the coating surface, and at this time, the hydrogel skeleton has a good absorption effect on moisture, and can keep the wound dry. At the same time, the first nano-cuttlebone powder with a larger particle size promotes the aggregation of platelets at the wound and accelerates the coagulation process. As time goes by, the effectiveness of the first nano-cuttlebone powder decreases, and the second nano-cuttlebone powder with a smaller particle size can be transferred between the particles of the first nano-cuttlebone powder, thereby providing fresh and effective cuttlebone, further promoting the coagulation process. Therefore, when the hydrogel wound dressing containing nano-cuttlebone of the present invention is used, as the dressing time increases, a high concentration of high-efficiency cuttlebone can be maintained at the dressing surface, thereby maintaining a lasting hemostatic effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the structure of a hydrogel wound dressing containing nano-cuttlebone in one embodiment of the present invention.
[0019] The marks in the figure are:
[0020] 100. Hydrogel wound dressing containing nano-cuttlebone; 101. Dressing body; 1011. First hydrogel skeleton; 1012. Second hydrogel skeleton; 1013. First nano-cuttlebone powder; 1014. Second nano-cuttlebone powder; 102. Waterproof and breathable membrane; 103. Protective membrane. DETAILED DESCRIPTION
[0021] The inventors of the present invention found in the process of studying wound dressings that hydrogel is a polymer material with a three-dimensional network structure, which can absorb a large amount of water, keep the wound moist, and is conducive to wound healing. At the same time, hydrogel also has good biocompatibility and air permeability, which can reduce the risk of wound infection. However, the hemostatic performance of hydrogel is poor. Cuttlebone has the effects of astringent hemostasis, astringent sperm and leukorrhea, acid relieving and analgesic, moisture astringent and sore astringent, and its effective ingredients can promote blood coagulation and have good hemostatic effects. Applying cuttlebone to wound dressings can improve the hemostatic effect of dressings. However, under normal circumstances, the dispersibility of cuttlebone powder in the dispersion medium is poor, and it is easy to agglomerate, which affects the performance of its hemostatic effect. If hydrogel and cuttlebone are used in combination, the hemostatic effect of wound dressings can be effectively improved.
[0022] Based on this, one embodiment of the present invention provides a hydrogel wound dressing containing nano-cuttlebone. Figure 1 According to one embodiment of the present invention, a hydrogel wound dressing 100 containing nano-cuttlebone is provided. The hydrogel wound dressing 100 containing nano-cuttlebone comprises a dressing body 101, wherein the dressing body 101 has a coating surface and an isolation surface opposite to the coating surface, wherein the coating surface is used to cover the wound, and the isolation surface is used to isolate the contact between the environment and the wound; in the direction from the coating surface to the isolation surface, the dressing body 101 comprises a first hydrogel skeleton 1011 and a second hydrogel skeleton 1012 which are stacked, wherein a first nano-cuttlebone powder 1013 is distributed in the first hydrogel skeleton 1011, and a second nano-cuttlebone powder 1014 is distributed in the second hydrogel skeleton 1012; and the particle size of the first nano-cuttlebone powder 1013 is larger than the particle size of the second nano-cuttlebone powder 1014.
[0023] When the wound dressing of this embodiment is used, the wound is covered by the dressing surface. At this time, the hydrogel skeleton has a good absorption effect on water, which can keep the wound dry. At the same time, the first nano-cuttlebone powder 1013 with a larger particle size promotes the aggregation of platelets at the wound and accelerates the coagulation process. As time goes by, the effectiveness of the first nano-cuttlebone powder 1013 decreases, and the second nano-cuttlebone powder 1014 with a smaller particle size can be transferred between the particles of the first nano-cuttlebone powder 1013, thereby providing fresh and effective cuttlebone, further promoting the coagulation process. Therefore, when the hydrogel wound dressing 100 containing nano-cuttlebone of the present invention is used, as the dressing time is extended, a high concentration of high-efficiency cuttlebone can be maintained at the dressing surface, thereby maintaining a lasting hemostatic effect.
[0024] Furthermore, the nano-cuttlebone powder has a good dispersion effect in the hydrogel skeleton, so that the first nano-cuttlebone powder 1013 in the first hydrogel skeleton 1011 can be evenly distributed in the first hydrogel skeleton 1011, and the second nano-cuttlebone powder 1014 in the second hydrogel skeleton 1012 can be evenly distributed in the second hydrogel skeleton 1012, which is conducive to giving full play to the efficacy of the nano-cuttlebone and further improving the hemostatic effect of the hydrogel wound dressing.
[0025] In the present invention, by distributing the cuttlebone powders of different particle sizes in the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012, the synergistic improvement of the hemostatic effect is achieved. In the early stage of the wound contacting the dressing, the first nano-cuttlebone powder 1013 with a large particle size plays a role in rapid and stable hemostasis, and the second nano-cuttlebone powder 1014 with a small particle size assists in enhancing the hemostatic effect. As time goes by, after the effectiveness of the first nano-cuttlebone powder 1013 with a large particle size decreases, the second nano-cuttlebone powder 1014 with a small particle size can be replenished in time and continue to play a hemostatic effect. This synergistic effect enables the hydrogel wound dressing containing nano-cuttlebone powders of different particle sizes to have a long-lasting and efficient hemostatic effect, providing good conditions for wound healing.
[0026] Furthermore, the inventors of the present invention have found through research on the hydrogel wound dressing 100 containing nano-cuttlebone that when the wound just contacts the hydrogel wound dressing 100 containing nano-cuttlebone, the first nano-cuttlebone powder 1013 with a large particle size takes effect first. Due to its relatively large particle size, a physical barrier can be quickly formed on the wound surface. This physical barrier is like a small "dam" that can stop the flow of blood. At the same time, the surface of the first nano-cuttlebone powder 1013 with a large particle size can adsorb a large number of platelets, and the platelets can release coagulation factors after aggregation on its surface to accelerate the coagulation process. In addition, since the particles of the first nano-cuttlebone powder 1013 with a large particle size are relatively large, they are not easily washed away by blood. Therefore, the physical barrier formed on the wound surface is relatively stable and can effectively play a hemostatic role in the early stage of the wound.
[0027] Furthermore, the second nano-cuttlebone powder 1014 with a small particle size has a small particle size and a larger specific surface area. In the early stage of the wound, the second nano-cuttlebone powder 1014 with a small particle size can be filled in the gaps between the first nano-cuttlebone powder 1013 with a large particle size, further enhancing the physical barrier effect. At the same time, the second nano-cuttlebone powder 1014 with a small particle size can also adsorb platelets, and due to its large specific surface area, the powder per unit mass can adsorb more platelets. In addition, the bioactive components contained in the second nano-cuttlebone powder 1014 with a small particle size can contact and react with the coagulation factors in the blood more quickly, assisting the first nano-cuttlebone powder 1013 with a large particle size to accelerate the coagulation rate.
[0028] As time goes by, the hemostatic effect of the first nano-cuttlebone powder 1013 with large particle size will gradually decrease. On the one hand, under the scouring and soaking of blood, the platelets adsorbed on the surface of the first nano-cuttlebone powder 1013 with large particle size may fall off, and its physical barrier effect will also be weakened due to the wear or displacement of the particles. On the other hand, the bioactive components in the first nano-cuttlebone powder 1013 with large particle size will gradually be consumed in the continuous coagulation reaction. As these effective components decrease, their ability to activate coagulation factors will also decrease, resulting in a slower coagulation process. However, the process of the first nano-cuttlebone powder 1013 with large particle size decreasing in effectiveness also creates conditions for the second nano-cuttlebone powder 1014 with small particle size to play a role. As the gaps between the large-sized first nano-cuttlebone powder 1013 particles become larger, the small-sized second nano-cuttlebone powder 1014 can be more easily transferred from the second hydrogel skeleton 1012 to the first nano-cuttlebone powder 1013 particles in the first hydrogel skeleton 1011, and continue to exert a good hemostatic effect. This dynamic replenishment process can ensure that there are always enough cuttlebone components at the wound to promote hemostasis for a long time.
[0029] Furthermore, the second nano-cuttlebone powder 1014 with a small particle size can penetrate into the tiny gaps of the wound tissue due to its small particle size and fully contact with the components in the blood. The second nano-cuttlebone powder 1014 with a small particle size can continue to adsorb platelets, activate coagulation factors, and maintain the coagulation process.
[0030] In some embodiments, the particle size of the first nano-cuttlebone powder 1013 is 200nm~400nm. The particle size of the second nano-cuttlebone powder 1014 is 50nm~100nm. Optionally, the particle size of the first nano-cuttlebone powder 1013 can be 200nm, 210nm, 220nm, 230nm, 240nm, 250nm, 260nm, 270nm, 280nm, 290nm, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, etc. It is understandable that the particle size of the first nano-cuttlebone powder 1013 can also be selected in the range of 200nm~400nm. Optionally, the particle size of the second nano-cuttlebone powder 1014 can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, etc. It is understandable that the particle size of the second nano-cuttlebone powder 1014 can also be selected in the range of 50nm to 100nm. The particle sizes of the first nano-cuttlebone powder 1013 and the second nano-cuttlebone powder within the corresponding range can make the two better adapted, so that the second nano-cuttlebone powder 1014 can be more timely added to the first nano-cuttlebone powder 1013 in the first hydrogel skeleton 1011, further improving the hemostatic effect of the hydrogel wound dressing.
[0031] In some embodiments, the mass percentage of the first nano-cuttlebone powder 1013 in the first hydrogel skeleton 1011 is greater than the mass percentage of the second nano-cuttlebone powder 1014 in the second hydrogel skeleton 1012. At this time, in the early stage of hemostasis, the wound dressing can provide enough cuttlebone components to promote hemostasis, so that the first nano-cuttlebone powder 1013 can fully exert the hemostatic effect and obtain a rapid hemostatic effect. At the same time, since a rapid hemostatic effect is obtained in the early stage of hemostasis, the impact of blood flow on the platelets adsorbed by the nano-cuttlebone powder can be reduced during the hemostasis process, which is more conducive to promoting the effect of the second nano-cuttlebone powder 1014, and is conducive to further improving the hemostatic effect of the hydrogel wound dressing.
[0032] In some embodiments, the mass percentage of the first nano-cuttlebone powder 1013 to the first hydrogel skeleton 1011 is 5% to 15%. The mass percentage of the second nano-cuttlebone powder 1014 to the second hydrogel skeleton 1012 is 2% to 10%. If the content of the nano-cuttlebone powder is too low, it may not provide enough coagulation promoting components, resulting in prolonged hemostasis time. At the same time, the addition of the nano-cuttlebone powder will change the internal structure of the hydrogel skeleton, and the appropriate amount of nano-cuttlebone powder can be used as a reinforcing phase to improve the strength of the hydrogel skeleton. However, if the content of the nano-cuttlebone powder is too high, it may affect the intrinsic properties of the hydrogel skeleton itself. For example, when the content of the nano-cuttlebone powder is too high, too many nanoparticles will limit the movement of the polymer chain, making the hydrogel skeleton stiff, which may reduce the elasticity of the hydrogel skeleton.
[0033] Optionally, the mass percentage of the first nano-cuttlebone powder 1013 in the first hydrogel skeleton 1011 may be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc. It is understood that the mass percentage of the first nano-cuttlebone powder 1013 in the first hydrogel skeleton 1011 may also be other suitable selections within the range of 5% to 15%. Optionally, the mass percentage of the second nano-cuttlebone powder 1014 in the second hydrogel skeleton 1012 may be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. It is understood that the mass percentage of the second nano-cuttlebone powder 1014 in the second hydrogel skeleton 1012 may also be other suitable selections within the range of 2% to 10%.
[0034] In some embodiments, the thickness of the first hydrogel skeleton 1011 is greater than the thickness of the second hydrogel skeleton 1012. The thicker first hydrogel skeleton 1011 can accommodate more first nano-cuttlebone powders 1013 with larger particle sizes, and can provide sufficient cuttlebone components to initiate a rapid hemostasis process when the wound is initially contacted. The thinner second hydrogel skeleton 1012 can make the second nano-cuttlebone powder 1014 have a shorter transfer distance, thereby increasing the transfer rate of the second nano-cuttlebone powder 1014 to the first hydrogel skeleton 1011, so that the second nano-cuttlebone powder 1014 can be replenished between the first nano-cuttlebone powder 1013 more quickly, promoting the continuation of hemostasis, and thereby improving the hemostatic effect of the hydrogel wound dressing.
[0035] In some embodiments, the thickness of the first hydrogel skeleton 1011 is 0.3 mm to 2 mm. The thickness of the second hydrogel skeleton 1012 is 0.2 mm to 1.5 mm. When the thickness of the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012 is too small, it is difficult to accommodate a sufficient amount of the first nano-cuttlebone powder 1013 and the second nano-cuttlebone powder 1014, thereby limiting the hemostatic effect. In addition, when the thickness of the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012 is too small, it is difficult to provide a physical barrier of sufficient strength for the wound, which increases the risk of secondary injury to the wound due to friction, collision, etc. At the same time, when the thickness of the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012 is too small, the isolation effect of external bacteria, dust and other pollutants is poor, which may cause external pollutants to easily invade the hydrogel wound dressing, thereby slowing down the healing of the wound. When the thickness of the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012 is too large, the overly thick hydrogel skeleton may cause the hydrogel wound dressing to not fit tightly to the wound, and easily produce gaps, providing space for bacteria to grow. At the same time, an overly thick hydrogel skeleton may reduce the air permeability of the wound dressing, slowing down the healing of the wound. In addition, when the thickness of the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012 is too large, the dressing will produce a more obvious foreign body sensation at the wound, resulting in a poor user experience.
[0036] Optionally, the thickness of the first hydrogel skeleton 1011 can be 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, 1.6mm, 1.7mm, 1.8mm, 1.9mm, 2mm, etc. It is understandable that the thickness of the first hydrogel skeleton 1011 can also be other suitable selections within the range of 0.3mm to 2mm. Optionally, the thickness of the second hydrogel skeleton 1012 can be 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm, etc. It is understandable that the thickness of the second hydrogel skeleton 1012 can also be selected in the range of 0.2 mm to 1.5 mm.
[0037] For superficial wounds, such as ruptured blisters, mild abrasions, etc., the thickness of the hydrogel skeleton can be relatively thin. Optionally, the thickness of the first hydrogel skeleton 1011 can be designed to be 0.5 mm to 1 mm, and the thickness of the second hydrogel skeleton 1012 can be designed to be 0.3 mm to 0.8 mm. Such a thickness can ensure that the nano-cuttlebone powder can play a hemostatic role without causing excessive pressure on the wound, and is conducive to the rapid healing of the wound.
[0038] For deep wounds, such as cuts and punctures, thicker hydrogel skeletons are needed to provide adequate protection and hemostasis. Optionally, the thickness of the first hydrogel skeleton 1011 can be designed to be 1 mm to 2 mm, and the thickness of the second hydrogel skeleton 1012 is 0.8 mm to 1.5 mm. The thicker first hydrogel skeleton 1011 can store more first nano-cuttlebone powder 1013 to cope with the massive bleeding that may occur in deep wounds; while the thicker second hydrogel skeleton 1012 ensures that there is enough second nano-cuttlebone powder 1014 for subsequent hemostasis.
[0039] For wound dressings used in the short term, such as disposable wound dressings, the thickness of the hydrogel skeleton can be appropriately reduced. This can reduce costs and material consumption while ensuring basic hemostasis and protection functions. Optionally, for some small-area, shallow wounds, in the short-term use dressing, the thickness of the first hydrogel skeleton 1011 can be 0.3mm~0.8mm, and the thickness of the second hydrogel skeleton 1012 can be 0.2mm~0.6mm.
[0040] For wound dressings used for a long time, such as dressings for chronic wound care, the thickness of the hydrogel skeleton needs to be appropriately increased. This is because during long-term use, the dressing needs to continue to provide hemostasis, protection, and wound healing functions. Optionally, the thickness of the first hydrogel skeleton 1011 is 1 mm to 2 mm, and the thickness of the second hydrogel skeleton 1012 is 0.8 mm to 1.5 mm to ensure that there is enough nano-cuttlebone powder and good physical barrier function.
[0041] In some embodiments, the first hydrogel skeleton 1011 contains a first hydrophilic polymer material and a first crosslinking agent; the first hydrophilic polymer material includes sodium alginate, and the first crosslinking agent includes calcium chloride. The second hydrogel skeleton 1012 contains a second hydrophilic polymer material and a second crosslinking agent; the second hydrophilic polymer material includes one or more of polyacrylamide and polyvinyl alcohol, and the second crosslinking agent includes glutaraldehyde. By selecting appropriate hydrophilic polymer materials and crosslinking agents, it is beneficial to obtain the first hydrogel skeleton 1011 and the second hydrogel skeleton 1012 with excellent performance.
[0042] Sodium alginate belongs to natural polysaccharide substances, has a wide range of sources, and has good biocompatibility and biodegradability. In the presence of calcium ions, sodium alginate can quickly form a gel, which is convenient for preparing a hydrogel wound dressing. In addition, sodium alginate also has certain antibacterial properties, which can reduce the risk of wound infection. At the same time, sodium alginate can effectively absorb and retain wound exudate, maintain a moist environment for the wound, and a moderately moist environment can promote cell migration, proliferation, and angiogenesis. Therefore, the first hydrogel skeleton 1011 includes sodium alginate, which can effectively promote wound healing. Calcium chloride can undergo an ionic crosslinking reaction with the carboxyl group in sodium alginate to form a gel, thereby forming a relatively stable first hydrogel skeleton 1011.
[0043] Polyacrylamide has good water absorption and biocompatibility, and can form a stable hydrogel structure. The amide groups on its molecular chain can form hydrogen bonds with water molecules, increasing the water retention of the hydrogel skeleton. In addition, polyacrylamide also has a certain viscoelasticity, can adapt to the shape changes of the wound, and provide good fit. Polyvinyl alcohol is non-toxic, biodegradable, and has good film-forming properties and mechanical strength. By blending or cross-linking with polyacrylamide, the properties of the hydrogel can be adjusted. In addition, polyvinyl alcohol hydrogel has a high transparency, which is convenient for observing the healing of the wound. Therefore, the second hydrogel skeleton 1012 includes polyacrylamide and polyvinyl alcohol, which can improve the fit, elasticity and observability of the hydrogel wound dressing. Glutaraldehyde can undergo a cross-linking reaction with groups such as amino groups in the second hydrophilic polymer material to form a stable three-dimensional network structure, thereby forming a relatively stable second hydrogel skeleton 1012.
[0044] In some embodiments, the mass percentage of the first cross-linking agent in the first hydrogel skeleton 1011 is 1% to 5%, and the mass percentage of the second cross-linking agent in the second hydrogel skeleton 1012 is 0.1% to 1%. The appropriate amount of cross-linking agent can achieve a better cross-linking effect while reducing the problem of excessive cross-linking and a large amount of cross-linking agent residue caused by excessive use of cross-linking agent.
[0045] Optionally, the mass percentage of the first cross-linking agent in the first hydrogel skeleton 1011 can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, etc. It is understood that the mass percentage of the first cross-linking agent in the first hydrogel skeleton 1011 can also be selected in the range of 1% to 5%. Optionally, the mass percentage of the second cross-linking agent in the second hydrogel skeleton 1012 can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc. It is understood that the mass percentage of the second cross-linking agent in the second hydrogel skeleton 1012 can also be selected in the range of 0.1% to 1%.
[0046] In some of the embodiments, the hydrogel wound dressing 100 containing nano-cuttlebone further comprises a waterproof breathable membrane 102. The waterproof breathable membrane 102 is located on the isolation surface; the material of the waterproof breathable membrane 102 comprises one or more of polytetrafluoroethylene and polyurethane. In the hydrogel wound dressing, it is necessary to prevent the hydrogel skeleton from excessively absorbing water and losing its original performance due to the entry of external moisture. A sufficient oxygen supply is conducive to the healing of the wound. Therefore, the provision of the waterproof breathable membrane 102 can make the wound dressing have better waterproof effect and breathability. When the waterproof breathable membrane 102 is selected, the low moisture permeability and continuous polymer structure of the materials in polytetrafluoroethylene and polyurethane can extend the permeation path of water molecules, thereby making the waterproof breathable membrane 102 have a good waterproof effect, and the microporous structure of the material can provide better breathability.
[0047] In some embodiments, the thickness of the waterproof breathable membrane 102 is 10 μm to 30 μm. The thickness of the waterproof breathable membrane 102 within this range can take into account better waterproofness and breathability. Optionally, the thickness of the waterproof breathable membrane 102 can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, etc. It is understandable that the thickness of the waterproof breathable membrane 102 can also be other suitable choices within the range of 10 μm to 30 μm.
[0048] In some embodiments, the hydrogel wound dressing 100 containing nano-cuttlebone further comprises a protective film 103; the protective film 103 is located on the application surface; the material of the protective film 103 comprises one or more of polyethylene and polypropylene. The protective film 103 can prevent the application surface of the hydrogel wound dressing from being contaminated.
[0049] In some embodiments, the thickness of the protective film 103 is 40 μm to 60 μm. Optionally, the thickness of the protective film 103 can be 40 μm, 42 μm, 45 μm, 48 μm, 50 μm, 52 μm, 55 μm, 58 μm, 60 μm, etc. It is understandable that the thickness of the protective film 103 can also be other suitable choices within the range of 40 μm to 60 μm.
[0050] Another embodiment of the present invention provides a method for preparing the above-mentioned hydrogel wound dressing 100 containing nano-cuttlebone. The preparation method comprises the following steps:
[0051] S101: mixing a first hydrophilic polymer material and a second hydrophilic polymer material with water respectively to obtain a first polymer solution and a second polymer solution respectively.
[0052] S102: Mix the first nano-cuttlebone powder 1013 with the first polymer solution to obtain a first hydrogel precursor solution. Mix the second nano-cuttlebone powder 1014 with the second polymer solution to obtain a second hydrogel precursor solution.
[0053] S103: adding the first hydrogel precursor liquid into the mold, cross-linking and shaping, and obtaining the first hydrogel skeleton 1011.
[0054] S104: adding the second hydrogel precursor solution to the first hydrogel skeleton 1011 , cross-linking and fixing, and obtaining the second hydrogel skeleton 1012 .
[0055] Optionally, the first nano-cuttlebone powder 1013 and the second nano-cuttlebone powder 1014 can be respectively obtained into corresponding particle sizes by ball milling.
[0056] Optionally, during cross-linking and shaping in S103, a first cross-linking agent is added to the first hydrogel precursor solution. During cross-linking and shaping in S104, a second cross-linking agent is added to the second hydrogel precursor solution.
[0057] Optionally, a waterproof and breathable membrane 102 is covered on a surface of the second hydrogel skeleton 1012 away from the first hydrogel skeleton 1011 .
[0058] Optionally, a protective film 103 is covered on a surface of the first hydrogel skeleton 1011 away from the second hydrogel skeleton 1012 .
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0060] For those skilled in the art, according to the concept of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A hydrogel wound dressing containing nano-cuttlebone, characterized in that: The dressing body comprises a dressing body, wherein the dressing body has a dressing surface and an isolation surface opposite to the dressing surface, wherein the dressing surface is used to cover the wound, and the isolation surface is used to isolate the contact between the environment and the wound; in the direction from the dressing surface to the isolation surface, the dressing body comprises a first hydrogel skeleton and a second hydrogel skeleton which are stacked, wherein a first nano-cuttlebone powder is distributed in the first hydrogel skeleton, and wherein a second nano-cuttlebone powder is distributed in the second hydrogel skeleton; and the particle size of the first nano-cuttlebone powder is larger than the particle size of the second nano-cuttlebone powder; The mass percentage of the first nano-cuttlebone powder in the first hydrogel skeleton is greater than the mass percentage of the second nano-cuttlebone powder in the second hydrogel skeleton; The mass percentage of the first nano-cuttlebone powder in the first hydrogel skeleton is 5% to 15%; the mass percentage of the second nano-cuttlebone powder in the second hydrogel skeleton is 2% to 10%.
2. The hydrogel wound dressing containing nano-cuttlebone according to claim 1, characterized in that: The particle size of the first nano-cuttlebone powder is 200nm-400nm; the particle size of the second nano-cuttlebone powder is 50nm-100nm.
3. The hydrogel wound dressing containing nano-cuttlebone according to claim 1, characterized in that: The thickness of the first hydrogel skeleton is greater than the thickness of the second hydrogel skeleton.
4. The hydrogel wound dressing containing nano-cuttlebone according to claim 3, characterized in that: The thickness of the first hydrogel skeleton is 0.3 mm to 2 mm; the thickness of the second hydrogel skeleton is 0.2 mm to 1.5 mm.
5. The hydrogel wound dressing containing nano-cuttlebone according to any one of claims 1 to 4, characterized in that: The first hydrogel skeleton contains a first hydrophilic polymer material and a first cross-linking agent; the first hydrophilic polymer material includes sodium alginate, and the first cross-linking agent includes calcium chloride; the second hydrogel skeleton contains a second hydrophilic polymer material and a second cross-linking agent; the second hydrophilic polymer material includes one or more of polyacrylamide and polyvinyl alcohol, and the second cross-linking agent includes glutaraldehyde.
6. The hydrogel wound dressing containing nano-cuttlebone according to claim 5, characterized in that: The mass percentage of the first cross-linking agent in the first hydrogel skeleton is 1% to 5%; the mass percentage of the second cross-linking agent in the second hydrogel skeleton is 0.1% to 1%.
7. The hydrogel wound dressing containing nano-cuttlebone according to any one of claims 1 to 4, characterized in that: The hydrogel wound dressing containing nano-cuttlebone further comprises a waterproof and breathable membrane; the waterproof and breathable membrane is located on the isolation surface; the material of the waterproof and breathable membrane comprises one or more of polytetrafluoroethylene and polyurethane.
8. The hydrogel wound dressing containing nano-cuttlebone according to any one of claims 1 to 4, characterized in that: The hydrogel wound dressing containing nano-cuttlebone further comprises a protective film; the protective film is located on the dressing surface; the material of the protective film comprises one or more of polyethylene and polypropylene.
Citation Information
Patent Citations
Hydrogel wound dressing for enhancing photo-thermal sterilization curative effect and monitoring pH value of wound as well as preparation method and application of hydrogel wound dressing
CN118286501A
aqueous hydrogel composition comprising elemental silver particles
DE102016125579A1